The Triple Logic of General Secretary Xi Jinping’s Important Thoughts on the Party’s Self-Revolution - Xu, Yangfei (International Journal of Social Sciences and Public Administration, 2025)
Self-revolution is the most distinctive political characteristic of the Communist Party of China (CPC) and its greatest strength. General Secretary Xi Jinping’s important thoughts on the Party’s self-revolution clearly propose the practical requirements of advancing self-revolution with “nine approaches.” These thoughts are the theoretical crystallization and essence of the era in Party building in the new era and serve as an important guide for advancing comprehensive and strict governance of the Party, Party conduct and integrity construction, and anti-corruption efforts. To understand General Secretary Xi Jinping’s important thoughts on the Party’s self-revolution, one must deeply grasp the historical logic, theoretical logic, and practical logic embedded within them, continually enhancing political consciousness, ideological awareness, and action consciousness in advancing self-revolution.